The Role of Organizational Culture as a Mediator Between the Influence of Motivation, Leadership, and Supply Chain Management on Employee Green Behavior - Agus Susanto (International Journal of Social Science and Business, 2023)
This research is motivated by the important role of companies in the context of globalization, where dependence between countries is increasing. The company is a vital element in meeting the needs of the global community. The main objective of this study is to analyze how organizational culture mediates the relationship between motivation, leadership, and supply chain management to employees' green behavior. The population of this study was employees of PT. X which has a total of 592 employees, the sampling technique used is simple random sampling so that a sample of 86 employees from PT. X. The research method used is quantitative research by applying Partial Least Squares (PLS) as a data analysis tool. The results showed that motivation and leadership had a significant and positive influence on employees' green behavior. Motivation also has a significant positive influence on employees' green behavior through mediating organizational culture. In addition, organizational culture also has a significant effect on the green behavior of employees at PT. X. in Indonesia. The results of this study have important implications in the context of human resource management that cares for the environment. These results can assist companies in developing strategies to improve employees' green behavior and achieve sustainability goals.